2023
DOI: 10.1038/s41598-023-27461-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of metabolic reprogramming by metabolomics in the oncocytic thyroid cancer cell line XTC.UC1

Abstract: Oncocytic thyroid cancer is characterized by the aberrant accumulation of abnormal mitochondria in the cytoplasm and a defect in oxidative phosphorylation. We performed metabolomics analysis to compare metabolic reprogramming among the oncocytic and non-oncocytic thyroid cancer cell lines XTC.UC1 and TPC1, respectively, and a normal thyroid cell line Nthy-ori 3-1. We found that although XTC.UC1 cells exhibit higher glucose uptake than TPC1 cells, the glycolytic intermediates are not only utilized to generate e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 63 publications
0
1
0
Order By: Relevance
“…Recent study compared oncocytic and non-oncocytic thyroid cancer, and revealed higher glucose uptake and rerouting of glutamine to glutathione for redox homeostasis in the oncocytic cell line to compensate for its defective mitochondrial function. 19) Moreover, 1 H-NMR spectroscopy has been used to show that oxidative stress alters the metabolic profile in thyroid cancer, with increases in lactate and aromatic amino acids and a decrease in citrate. 18) However, the de novo serine biosynthetic pathway from glucose is not fully understood in differentiated thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recent study compared oncocytic and non-oncocytic thyroid cancer, and revealed higher glucose uptake and rerouting of glutamine to glutathione for redox homeostasis in the oncocytic cell line to compensate for its defective mitochondrial function. 19) Moreover, 1 H-NMR spectroscopy has been used to show that oxidative stress alters the metabolic profile in thyroid cancer, with increases in lactate and aromatic amino acids and a decrease in citrate. 18) However, the de novo serine biosynthetic pathway from glucose is not fully understood in differentiated thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These defects have been studied in oncocytic thyroid cancer, which is characterized by the accumulation of abnormal mitochondria in the cytoplasm. Recently, a study comparing oncocytic and non-oncocytic thyroid cancer, showed higher glucose uptake and rerouting of glutamine to glutathione for redox homeostasis in the oncocytic cell line to compensate for its defective mitochondrial function [50]. 1 H-NMR spectroscopy has been used to show that oxidative stress alters the metabolic prowww.e-enm.org 623 file in thyroid cancer, with increases in lactate and aromatic amino acids and a decrease in citrate [51].…”
Section: Metabolism In Thyroid and Other Cancersmentioning
confidence: 99%